Beyond the maze : streamlining labour recruitment process in Bangladesh - Siddiqui, Tasneem; Refugee and Migratory Movements Research Unit. (Dhaka : Refugee and Migratory Movements Research Unit, 2002)
Contributed articles at workshop.
In English; part in Bengali.
Includes bibliographical references (p. [152]-[153]).
Keywords: Foreign workers, Bengladeshi -- Recruiting -- Foreign countries -- Congresses; Labor supply -- Bangladesh -- Congresses; Employees -- Recruiting -- Bangladesh -- Congresses